2020
DOI: 10.1093/hmg/ddaa069
|View full text |Cite
|
Sign up to set email alerts
|

Different gene expression profiles in iPSC-derived motor neurons from ALS8 patients with variable clinical courses suggest mitigating pathways for neurodegeneration

Abstract: Amyotrophic lateral sclerosis type 8 (ALS8) is an autosomal dominant form of ALS, which is caused by pathogenic variants in the VAPB gene. Here we investigated five ALS8 patients, classified as ‘severe’ and ‘mild’ from a gigantic Brazilian kindred, carrying the same VAPB mutation but displaying different clinical courses. Copy number variation and whole exome sequencing analyses in such individuals ruled out previously described genetic modifiers of pathogenicity. After deriving induced pluripotent stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
3
12
1
Order By: Relevance
“…Such data suggested that unknown genetic modifiers might be playing a role in disease progression in these ALS8 patients (Oliveira et al, 2020).…”
Section: Searching For Modifying Mechanisms In Als8mentioning
confidence: 93%
See 4 more Smart Citations
“…Such data suggested that unknown genetic modifiers might be playing a role in disease progression in these ALS8 patients (Oliveira et al, 2020).…”
Section: Searching For Modifying Mechanisms In Als8mentioning
confidence: 93%
“…Here we describe different aspects of ALS8 clinical variability, both in terms of clinical manifestations and in rate of disease progression. Then, we outline our recent work on ALS8 patients (Oliveira et al, 2020), in which we tried to address the molecular underpinnings of clinical progression variation in the patients we studied. We were able to rule out well-described genetic modifiers, such as EPHA4 and UNC13A, and potential copy number variation alterations.…”
Section: Phenotypic Heterogeneity In Amyotrophic Lateral Sclerosis Anmentioning
confidence: 99%
See 3 more Smart Citations